2021
DOI: 10.1111/jocs.15621
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for heart transplant survival with greater than 5 h of donor heart ischemic time

Abstract: Objective Implantation of donor hearts with prolonged ischemic times is associated with worse survival. We sought to identify risk factors that modulate the effects of prolonged preservation. Methods Retrospective review of the United Network for Organ Sharing database (2000–2018) to identify transplants with >5 (n = 1526) or ≤5 h (n = 35,733) of donor heart preservation. In transplanted hearts preserved for >5 h, Cox‐proportional hazards identify modifiers for survival. Results Compared to ≤5 h, transplanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Tang et al 1 demonstrated that a pre-transplant use of extracorporeal membrane oxygenation, pre-transplant dependence on dialysis, and ischemic etiology for heart failure was associated with further risk of mortality in the heart transplant recipients who received donor hearts with prolonged ischemic time. Several concerns have been raised.…”
Section: Implication Of Prolonged Ischemic Time Of Donor Heart For the Heart Transplant Recipientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tang et al 1 demonstrated that a pre-transplant use of extracorporeal membrane oxygenation, pre-transplant dependence on dialysis, and ischemic etiology for heart failure was associated with further risk of mortality in the heart transplant recipients who received donor hearts with prolonged ischemic time. Several concerns have been raised.…”
Section: Implication Of Prolonged Ischemic Time Of Donor Heart For the Heart Transplant Recipientsmentioning
confidence: 99%
“…In their study, patients using donor hearts with >5 h of preservation time were sicker than those with the shorter ischemic time of the donor's hearts. 1 It might be better to perform multivariate analysis to validate independence in the prognostic impact of prolonged ischemic time by adjusting for other potential confounders.…”
Section: Implication Of Prolonged Ischemic Time Of Donor Heart For the Heart Transplant Recipientsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the more than five donor heart group, this revealed independent factors associated with mortality to be pretransplant extracorporeal membrane oxygenation (ECMO), pretransplant dialysis, ischemic etiology for heat failure and O blood type donor hearts. 1 While these recipient and donor risk factors are largely nonmodifiable, there are developing molecular therapeutic strategies to increase the resilience of donor hearts to ischemic injury during preservation as well as introduction into a hostile recipient. Research is currently underway to inhibit inflammatory (e.g., inflammasome) and cell death pathways that occur during cold storage and in the setting of deceased cardiac death donation.…”
Section: Reply To Lettermentioning
confidence: 99%
“…A multivariable analysis was then performed on variables found to be significant on univariable analysis. For the more than five donor heart group, this revealed independent factors associated with mortality to be pretransplant extracorporeal membrane oxygenation (ECMO), pretransplant dialysis, ischemic etiology for heat failure and O blood type donor hearts 1 …”
mentioning
confidence: 99%